1998
DOI: 10.1111/j.1559-1816.1998.tb01707.x
|View full text |Cite
|
Sign up to set email alerts
|

When Physical Disabilities Are Not Liabilities: The Role of Applicant and Interviewer Characteristics on Employment Interview Outcomes

Abstract: An applied sample was randomly assigned to evaluate the credentials of a job candidate with or without a physical disability and whose interview responses varied in quality (positive vs. average vs. negative). In addition to making hiring decisions, participants completed a number of measures including the Marlowe‐Crowne Social Desirability Scale (Crowne & Marlowe, 1964), the Interaction with Disabled Persons Scale (Gething, 1991), an interview comfort measure, and an EEOC knowledge quiz. Results consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Roberts & Macan, 2006). There is also direct evidence indicating a relationship between interviewer's level of comfort when interacting with persons with disabilities and their evaluations of the interview performance of such individuals (Nordstrom et al, 1998). It seems likely that the media may also have some beneficial role to play, given evidence that exposure to positive exemplars of a discriminated-against minority has the effect of reducing automatic, implicit prejudice against members of that social group (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roberts & Macan, 2006). There is also direct evidence indicating a relationship between interviewer's level of comfort when interacting with persons with disabilities and their evaluations of the interview performance of such individuals (Nordstrom et al, 1998). It seems likely that the media may also have some beneficial role to play, given evidence that exposure to positive exemplars of a discriminated-against minority has the effect of reducing automatic, implicit prejudice against members of that social group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There have been When your face doesn't fit Page 5 of 40 several reports of positive bias towards a fictional job applicant with impaired mobility from undergraduate students (Gouvier, Sytsma-Jordan & Mayville, 2003) or employees (Bell & Klein, 2001;Christman & Slaten, 1991;Nordstrom, Huffaker & Williams, 1998; but see also Colella, DeNisi & Varma, 1998). Turning to facial disfigurement, Stevenage and McKay (1999) reported a study in which recruitment consultants stated a 100% likelihood of employing an applicant with a facial disfigurement (port wine stain) for a general administrative position.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Drehmer and Bordieri (1985), supervisors and midlevel managers reviewing resumes rated an applicant described as having a physical handicap as more favorable than a comparable applicant without a disability. Studies using videotapes of mock employment interviews also found more positive ratings for applicants with a physical disability than for equally-qualified applicants without a physical disability (Cesare, Tannenbaum, & Dalessio, 1990;Christman & Branson, 1990;Christman & Slaten, 1991;Nordstrom, Huffaker, & Williams, 1998).…”
mentioning
confidence: 90%
“…Millington, Reid and Leierer (1997) reported people with disabilities to be rated higher than individuals without disabilities applying for the same position in terms of satisfactoriness, job knowledge, trainability, dependability and motivation. Social desirability appeared not to be an influence on employer self-reported attitudes toward hiring people with disabilities (Nordstrom et al, 1998).…”
Section: Positive Attitudes Toward Hiring and Accommodationsmentioning
confidence: 99%